Immunoprotein deposition in synovial tissue in Reiter's syndrome. Issue 3 (June 1981) - Baldassare, A R; Weiss, T D; Tsai, C C; Arthur, R E; Moore, T L; Zuckner, J
Abstract : The aetiology of Reiter's syndrome (RS) is unknown. In order to evaluate the role of immunological mechanisms in this disease we performed synovial biopsies on 12 patients with RS looking for deposition of immunoglobulins and complement components in synovial tissue. By immunofluorescent techniques 11 synovia were found to have immunoprotein deposition. IgM deposition was found around vessels in 8 synovia and in the interstitial tissue in 4. C3 was present perivascularly in 11 cases; in 4 of those there was also staining in the interstitial tissue. No immunoproteins were found in infiltrating or synovial lining cells. The finding of immunoproteins in the synovium of the majority of patients with RS suggests that immunological mechanisms are involved in the pathogenesis of this disease.